Chiral nano composite material for hydroxyl radical dual-signal sensing, preparation method and application of chiral nano composite material

By developing chiral nanocomposites UCNPs@L-POM, L-cysteine ​​is used to reduce oxidized molybdenum-based polyoxometalate and coated on the surface of upconversion nanoparticles, solving the problem of real-time monitoring of hydroxyl radicals in the body. , achieving high-sensitivity upconversion luminescence/circular dichroism dual signal sensing to meet the needs of early diagnosis of rheumatoid arthritis.

CN119351105APending Publication Date: 2025-01-24JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411483235.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art is difficult to monitor the typical biomarker hydroxyl radicals of rheumatoid arthritis in real time and continuously in vivo, and the selectivity and availability of chiral nanocomposites in biomedical diagnosis and detection are limited.

Method used

Develop a handiconal nano-composite material UCNPS@L-POM. Through L-cysteine ​​as a reducing agent and a hand ligand, the oxidized molybdenum album-based metal oxygen is restored and covered on the surface of the altable nanoparticles It forms a material that can transform the light/round dual -color dual signal response under the existence of the hydroxyl radicals.

Benefits of technology

A high -sensitivity dual signal sensing of hydroxyl free radicals can be monitored in real time in the body to monitor the level of hydroxyl radicals, meet the needs of early diagnosis of rheumatoid arthritis, and enlarge the selection of detection through the level of the index of hand signal. And availability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351105A_ABST
    Figure CN119351105A_ABST
Patent Text Reader

Abstract

The invention discloses a chiral nano composite material for hydroxyl radical double-signal sensing, a preparation method and application thereof, and belongs to the technical field of sensing. Comprising the following steps: synthesis of up-conversion nanoparticles with a core-shell structure, preparation of hydrophilic up-conversion nanoparticles, preparation of oxidation-state molybdenum-based polyoxometallate nanoparticles, preparation of a chiral nanocomposite UCNPs (at) L-POM and the like. According to the preparation method, L-cysteine is used as a reducing agent and a chiral ligand, oxidation-state molybdenum-based polyoxometallate is reduced and coats the surfaces of up-conversion nano particles, and the UCNPs (at) L-POM chiral nano composite material is formed. In the presence of hydroxyl radicals, Mo < 4 + > in the composite material is oxidized into Mo < 5 + >, and generated absorption quenches up-conversion luminescence. Meanwhile, the circular dichroism signal is reduced due to the dissociation of the L-cysteine, so that the composite material can generate up-conversion luminescence / circular dichroism double-signal response aiming at hydroxyl free radicals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of sensing technology, and specifically relates to a chiral nanocomposite material for hydroxyl radical dual-signal sensing, a preparation method and its application in dual-signal sensing of hydroxyl radical upconversion luminescence and circular dichroism signals (i.e., upconversion luminescence / circular dichroism dual-signal response). Background Art

[0002] The concept of chirality was proposed during the study of the crystallography and optical activity of natural tartaric acid and its related substances. Subsequently, it was found that many biomolecules such as glucose, amino acids, proteins and DNA exhibit chirality. With the in-depth study of chiral light-matter interactions, sensing based on circular dichroism (CD) spectroscopy has gradually become one of the important characteristics of chiral biosensors. However, the CD signals of natural biomolecules (such as amino acids) are usually weak, and high concentrations of samples are required to accurately characterize the chirality of molecules, which increases the detection cost and reduces the sensitivity. In recent years, with the development of nanotechnology, scientists have used chiral biomolecules to transfer chirality to larger submicron nanomaterials and designed a large number of artificial chiral nanomaterials that exhibit amplified chiral signals. This enhanced chiral activity is very sensitive to changes in the material structure, which means that even small changes in the structure of the nanomaterial will lead to precise changes in the CD signal. This property gives these materials significant advantages in ultrasensitive bioassay applications, but their biological applications are currently limited to in vitro detection and cannot meet the requirements of real-time and continuous monitoring of diseases in vivo.

[0003] Given the importance of in situ visualization in biological applications, scientists have combined chirality with other optical properties to construct chiral nanocomposites with a variety of biofunctional properties. Compared with traditional single-signal chiral materials, these chiral nanocomposites have richer functions, but due to the limitations of material types and preparation techniques, the selectivity and availability of chiral nanocomposites are still greatly limited. Therefore, the development of chiral nanocomposites with stable structures and excellent performance to meet the needs of biomedical diagnosis and detection has important research significance and practical application value.

[0004] Hydroxyl radicals are the typical biomarker of rheumatoid arthritis. They have high oxidative reactivity and are the most harmful reactive oxygen species. Therefore, it is important to develop technologies to monitor hydroxyl radical (·OH) levels in order to diagnose these serious diseases at an early stage. Summary of the invention

[0005] The purpose of the present invention is to provide a chiral nanocomposite material for dual-signal sensing of hydroxyl radicals, a preparation method thereof, and its application in dual-signal sensing of upconversion luminescence and circular dichroism signals of hydroxyl radicals (i.e., upconversion luminescence / circular dichroism dual-signal response). The present invention aims to use chiral biomolecules to induce nanoscale materials to produce new chiral properties, and prepare UCNPs@L-POM chiral nanocomposite materials, which can produce upconversion luminescence / circular dichroism dual-signal response for hydroxyl radicals.

[0006] The preparation method of a chiral nanocomposite material for hydroxyl radical dual signal sensing according to the present invention comprises the following steps:

[0007] (1) Synthesis of NaErF4:0.5% Tm@NaLuF4 upconversion nanoparticles with core-shell structure: 0.995mmol ErCl3·6H2O, 0.005mmol TmCl3·6H2O, 14mL 1-octadecene and 6mL oleic acid were mixed and stirred for 20-40 minutes, and the resulting solution was heated to 150-160°C and stirred for 20-40 minutes until the solid dissolved in the solution; then the solution was naturally cooled to 45-55°C and 10mL methanol solution containing 2.50mmol sodium hydroxide and 4.00mmol ammonium fluoride was added, and the solution was heated to 65-75°C and stirred for 20-40 minutes until the methanol was completely removed; the resulting mixture was heated to 300-320°C and reacted for 60-70 minutes. After the reaction, the solution was naturally cooled to 45-55°C, washed with acetone and ethanol, and centrifuged to obtain NaErF4:0.5% Tm bare core upconversion nanoparticles; finally, the obtained bare core upconversion nanoparticles were dissolved in 8 mL of cyclohexane for standby use, and the concentration of the bare core upconversion nanoparticles was 125 mM; during the entire experiment, nitrogen flow was ensured to remove oxygen in the reaction system;

[0008] 0.50mmol LuCl3·6H2O, 7mL 1-octadecene and 3mL oleic acid were mixed and stirred for 20-40 minutes, and the obtained solution was heated to 150-160°C and stirred for 20-40 minutes until the solid in the solution was dissolved; after naturally cooling to 45-55°C, 4mL 125mM NaErF4:0.5% Tm naked core upconversion nanoparticles cyclohexane solution was added, and the temperature was raised to 80-90°C and stirred for 20-40 minutes until the cyclohexane was completely removed; after naturally cooling to 45-55°C, 5mL methanol solution containing 1.25mmol sodium hydroxide and 2.00mmol ammonium fluoride was added, and the temperature was heated to 65-75°C and stirred for 20-40 minutes until the methanol was completely removed; then the solution was heated to 300-320°C and reacted for 60-70 minutes. After the reaction, the solution was naturally cooled to 45-55°C, washed with acetone and ethanol, and centrifuged to obtain NaErF4:0.5% Tm@NaLuF4 core-shell structure upconversion nanoparticles; finally, the obtained core-shell structure upconversion nanoparticles were dissolved in 4 mL of cyclohexane for standby use, and the concentration of the core-shell structure upconversion nanoparticles was 125 mM; during the entire experiment, nitrogen flow was ensured to remove oxygen in the reaction system;

[0009] (2) Preparation of hydrophilic NaErF4: 0.5% Tm@NaLuF4 upconversion nanoparticles: First, add 2 mL of 125 mM NaErF4: 0.5% Tm@NaLuF4 core-shell structure upconversion nanoparticles cyclohexane solution obtained in step (1) to 2 mL of 0.1 M dilute hydrochloric acid aqueous solution, and stir for 8 to 12 hours to remove oleic acid ligands; then add acetone to precipitate ligand-free hydrophilic NaErF4: 0.5% Tm@NaLuF4 upconversion nanoparticles (UCNPs), collect by centrifugation, and disperse in 4 mL of deionized water to obtain an aqueous solution of UCNPs, wherein the concentration of the ligand-free hydrophilic NaErF4: 0.5% Tm@NaLuF4 upconversion nanoparticles is 62.5 mM;

[0010] (3) Preparation of oxidized molybdenum-based polyoxometalate (Ox-POM) nanoparticles: 1 mmol (1.23586 g) of (NH4)6Mo7O 24 4H2O was dissolved in 10mL of deionized water, and 0.6mmol (0.07196g) of NaH2PO4 was dissolved in 5mL of deionized water; the two solutions were then mixed and stirred for 20-40 minutes to form Ox-POM nanoparticles; the Ox-POM nanoparticles were precipitated with 50mL of ethanol, and the Ox-POM nanoparticle precipitate was collected after centrifugation at 8000-12000rpm for 5-15min, and the obtained Ox-POM nanoparticles were then vacuum dried at 50-70°C overnight;

[0011] (4) Preparation of chiral nanocomposite UCNPs@L-POM: 10 mg of dried Ox-POM nanoparticles obtained in step (3) were dissolved in 1600 μL of deionized water, 400 μL of 62.5 mM UCNPs aqueous solution obtained in step (2) was added and stirred for 3 to 10 min, then 8 mL of 31.25 mg / mL L-Cys aqueous solution was added and ultrasonication was continued for 10 to 20 minutes, the obtained UCNPs@L-POM solution was allowed to stand for 2 to 4 days, and UCNPs@L-POM powder was obtained after freeze-drying;

[0012] (5) Take the UCNPs@L-POM powder obtained in step (4) and add deionized water to prepare 1 mL, 5 mg / mL UCNPs@L-POM aqueous solution, add 1 mL, 10-800 μM hydroxyl radical aqueous solution thereto, and prepare 2 mL of standard solution; react the standard solution at room temperature for 20-30 minutes, and then measure the upconversion emission spectrum of the standard solution; establish a "relationship curve between hydroxyl radical concentration and upconversion luminescence intensity"; or take the UCNPs@L-POM powder obtained in step (4) and add deionized water to prepare 1 mL, 5 mg / mL UCNPs@L-POM aqueous solution, add 1 mL, 1-80 μM hydroxyl radical aqueous solution thereto, and prepare 2 mL of standard solution; react the standard solution at room temperature for 20-30 minutes, and then measure the circular dichroism spectrum of the standard solution; establish a "relationship curve between hydroxyl radical concentration and circular dichroism signal intensity"; the integral wavelength range of the upconversion luminescence intensity is 600-700 nm, and the circular dichroism signal intensity is the absolute value of the circular dichroism signal peak at 385 nm;

[0013] (6) Take the UCNPs@L-POM powder prepared in step (4) and add deionized water to prepare a 1 mL, 5 mg / mL UCNPs@L-POM aqueous solution, add 1 mL of a hydroxyl radical solution of unknown concentration thereto, and obtain 2 mL of a test solution; react the test solution at room temperature for 20 to 30 minutes, and then measure the upconversion emission spectrum and circular dichroism spectrum of the test solution respectively; substitute the upconversion fluorescence intensity and the circular dichroism signal intensity into the "hydroxyl radical concentration vs. upconversion luminescence intensity" relationship curve and the "hydroxyl radical concentration vs. circular dichroism signal intensity" relationship curve obtained in step (5), respectively, to calculate the concentration of hydroxyl radicals; the integral wavelength range of the upconversion luminescence intensity is 600 to 700 nm, and the circular dichroism signal intensity is the absolute value of the circular dichroism signal peak at 385 nm.

[0014] The chiral nanocomposite material for dual-signal sensing of hydroxyl radicals described in the present invention is prepared by the above method.

[0015] Working principle:

[0016] The present invention uses L-cysteine ​​as a reducing agent and chiral ligand to reduce the oxidized molybdenum-based polyoxometalate and coat it on the surface of upconversion nanoparticles to form UCNPs@L-POM chiral nanocomposite materials. In the presence of hydroxyl radicals, the Mo in the composite material 4+ Oxidized to Mo 5+ The absorption generated quenches the upconversion luminescence. At the same time, the dissociation of L-cysteine ​​leads to a decrease in the circular dichroism signal, enabling the composite material to produce an upconversion luminescence / circular dichroism dual signal response to hydroxyl radicals.

[0017] The chiral nanocomposite material UCNPs@L-POM prepared by the present invention for dual-signal sensing of hydroxyl radicals has the following advantages:

[0018] 1. The designed UCNPs@L-POM uses L-cysteine ​​as a reducing agent and chiral ligand to coat the oxidized molybdenum-based polyoxometalate on the surface of upconversion nanoparticles. This coating process is a self-assembly process with a simple preparation process and no complicated steps and operations are required;

[0019] 2. Using chiral L-Cys to transfer chirality to submicron UCNPs@L-POM, exponential amplification of chiral signals was achieved;

[0020] 3.UCNPs@L-POM has both upconversion luminescence signal and circular dichroism signal. The former can realize signal visualization, and the latter has higher sensitivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 : A schematic diagram of the preparation process and sensing principle of a chiral nanocomposite material for dual-signal sensing of hydroxyl radicals according to the present invention;

[0022] like Figure 1 As shown in the figure, hydrophilic core-shell NaErF4: 0.5% Tm@NaLuF4 upconversion nanoparticles (UCNPs) were first prepared; oxidized molybdenum-based polyoxometalate (Ox-POM) nanoparticles and L-cysteine ​​(L-Cys) were added to the upconversion nanoparticle solution, and under the action of L-Cys, Ox-POM was reduced and coated on UCNPs to form UCNPs@L-POM chiral nanocomposites. In the presence of hydroxyl radicals, the Mo in the composite material 4+ Oxidized to Mo 5+, the absorption generated quenches the upconversion luminescence. At the same time, the dissociation of L-cysteine ​​leads to a decrease in the circular dichroism signal, so that the composite material can produce an upconversion luminescence / circular dichroism dual signal response to hydroxyl radicals, so that the relationship between the hydroxyl radical concentration and the upconversion luminescence intensity and the circular dichroism signal intensity can be established to detect hydroxyl radicals.

[0023] Figure 2 : Transmission electron microscopy image of the UCNPs@L-POM chiral nanocomposite prepared in Example 4. The five spherical nanoparticles in the image are upconversion nanoparticles, and the light-colored polymer-like substance between the upconversion nanoparticles is L-POM, which coats the upconversion nanoparticles together;

[0024] Figure 3 : Circular dichroism spectra of L-Cys and UCNPs@L-POM in detection example 1. It can be seen from the figure that the circular dichroism spectrum intensity of UCNPs@L-POM composite nanomaterials is significantly enhanced compared with the circular dichroism spectrum intensity of pure L-Cys;

[0025] Figure 4 :Up-conversion luminescence spectra of UCNPs@L-POM chiral nanocomposites in different concentrations of hydroxyl radical solutions in Example 2 ( Figure 4 a) and the relationship curve between hydroxyl radical concentration and upconversion luminescence intensity ( Figure 4 b). Figure 4 It shows that with the increase of hydroxyl radical concentration, more Mo 4+ Oxidized to Mo 5+ , the quenching effect on upconversion luminescence is enhanced, resulting in the weakening of upconversion luminescence of UCNPs@L-POM chiral composite nanomaterials;

[0026] Figure 5 : Circular dichroism spectra of UCNPs@L-POM chiral nanocomposites in different concentrations of hydroxyl radical solutions in detection example 3 ( Figure 5 a) and the relationship curve between hydroxyl radical concentration and circular dichroism signal intensity ( Figure 5 b). Figure 5 It shows that with the increase of hydroxyl radical concentration, the chiral ligand L-Cys is stripped, resulting in the weakening of the circular dichroism signal intensity of UCNPs@L-POM chiral composite nanomaterials. DETAILED DESCRIPTION

[0027] Example 1: Synthesis of core-shell NaErF4:0.5% Tm@NaLuF4 upconversion nanoparticles

[0028] (1) 0.995mmol ErCl3·6H2O, 0.005mmol TmCl3·6H2O, 14mL 1-octadecene and 6mL oleic acid were mixed in a flask and stirred for 30 minutes, and the resulting solution was heated to 155°C and stirred for 30 minutes until the solid in the solution dissolved; after the solution was naturally cooled to 50°C, 10mL of a methanol solution containing 2.50mmol sodium hydroxide and 4.00mmol ammonium fluoride was added, and the mixture was heated to 70°C and stirred for 30 minutes until the methanol was completely removed; the mixture was then heated to 310°C and reacted for 65 minutes; after the reaction was completed, the solution was naturally cooled to 50°C, washed with acetone and ethanol, and centrifuged to obtain NaErF4:0.5% Tm bare core upconversion nanoparticles; finally, the obtained bare core upconversion nanoparticles were dissolved in 8mL cyclohexane for standby use, and the concentration of the bare core upconversion nanoparticles was 125mM; during the entire experiment, nitrogen flow was ensured to remove oxygen in the reaction system;

[0029] (2) A mixture of 0.50 mmol LuCl3·6H2O, 7 mL 1-octadecene and 3 mL oleic acid was mixed in a flask and stirred for 30 minutes, and the resulting solution was heated to 155°C and stirred for 30 minutes until the solid in the solution dissolved; after the temperature was naturally cooled to 50°C, 4 mL of a cyclohexane solution of 125 mM NaErF4:0.5% Tm naked core upconversion nanoparticles was added, and the temperature was raised to 85°C and stirred for 30 minutes until the cyclohexane was completely removed; after the temperature was naturally cooled to 50°C, 5 mL of a methanol solution containing 1.25 mmol sodium hydroxide and 2.00 mmol ammonium fluoride was added, and the temperature was heated to 70°C and stirred for 30 minutes until the methanol was completely removed; then the solution was heated to 310°C and reacted for 65 minutes; after the reaction was completed, the solution was naturally cooled to 50°C, washed with acetone and ethanol, and centrifuged to obtain NaErF4:0.5% Tm@NaLuF4 core-shell structure upconversion nanoparticles; finally, the obtained core-shell structure upconversion nanoparticles were dissolved in 4 mL of cyclohexane for standby use, and the concentration of the core-shell structure upconversion nanoparticles was 125 mM; during the entire experimental process, nitrogen flow was ensured to remove oxygen in the reaction system.

[0030] Example 2: Preparation of hydrophilic NaErF4:0.5% Tm@NaLuF4 upconversion nanoparticles

[0031] First, 2 mL of NaErF4:0.5% Tm@NaLuF4 core-shell structure upconversion nanoparticles cyclohexane solution was added to 2 mL of 0.1 M dilute hydrochloric acid aqueous solution and stirred for 10 hours to remove oleic acid ligands; then acetone was added to precipitate ligand-free hydrophilic NaErF4:0.5% Tm@NaLuF4 upconversion nanoparticles (UCNPs), which were collected by centrifugation and dispersed in 4 mL of deionized water to obtain an aqueous solution of UCNPs, in which the concentration of ligand-free hydrophilic NaErF4:0.5% Tm@NaLuF4 upconversion nanoparticles was 62.5 mM.

[0032] Example 3: Preparation of Oxidized Molybdenum-Based Polyoxometalate (Ox-POM) Nanoparticles

[0033] (1) 1.23586 g (NH4)6Mo7O 24 ·4H2O was dissolved in 10mL of deionized water, 0.07196g of NaH2PO4 was dissolved in 5mL of deionized water, and the two solutions were mixed and stirred for 30 minutes to form Ox-POM nanoparticles. After the reaction was completed, the Ox-POM nanoparticles were precipitated with 50mL of ethanol, and the Ox-POM nanoparticle precipitate was collected by centrifugation at 10,000rpm for 8min, and then the prepared Ox-POM nanoparticles were vacuum dried at 60°C overnight.

[0034] Example 4: Preparation of chiral nanocomposite UCNPs@L-POM

[0035] (1) 10 mg Ox-POM was dissolved in 1600 μL deionized water, 400 μL 62.5 mM UCNPs aqueous solution was added and stirred for 5 min, then 8 mL 31.25 mg / mL L-Cys aqueous solution was added and ultrasonication was continued for 15 min. The obtained UCNPs@L-POM aqueous solution was allowed to stand for 3 days and then freeze-dried to obtain UCNPs@L-POM powder (0.2417 g), i.e., a chiral nanocomposite material for dual-signal sensing of hydroxyl radicals.

[0036] Detection Example 1: Comparison of circular dichroism signals between L-Cys and chiral nanocomposite UCNPs@L-POM

[0037] Prepare 2 mL of 25 mg / mL L-Cys aqueous solution, and then take 2 mL of the UCNPs@L-POM aqueous solution after standing for 3 days in Example 4 (before standing and freeze-drying), measure the circular dichroism spectra of the above two solutions, and compare the circular dichroism signal intensity of pure L-Cys and UCNPs@L-POM formed after chiral transfer. Test Example 2: Upconversion luminescence signal sensing of hydroxyl radicals by chiral nanocomposite UCNPs@L-POM in aqueous solution

[0038] To a 1 mL, 5 mg / mL aqueous solution of chiral nanocomposite UCNPs@L-POM, 1 mL of aqueous hydroxyl radical solution of known concentrations (10, 80, 200, 400, 600, 800 μM) was added (the aqueous hydroxyl radical solution was generated by the Fenton reaction and was prepared by mixing equal volumes of Fe 2+ The aqueous solution and H2O2 aqueous solution were prepared, and the hydroxyl radical concentration was based on Fe 2+ The final concentration is taken as the basis) to prepare a 2 mL standard solution; the standard solution is reacted at room temperature for 25 minutes, and then the up-conversion emission spectrum of the standard solution is measured; a relationship curve of "hydroxyl radical concentration and up-conversion luminescence intensity" is established, and the integral wavelength range of the up-conversion luminescence intensity is 600-700 nm.

[0039] Detection Example 3: Circular dichroism signal sensing of hydroxyl radicals by chiral nanocomposite UCNPs@L-POM in aqueous solution

[0040] To 1 mL of chiral nanocomposite UCNPs@L-POM aqueous solution (5 mg / mL), 1 mL of hydroxyl radical aqueous solution with different known concentrations (1, 5, 10, 20, 60, 80 μM) was added (the hydroxyl radical aqueous solution was generated by Fenton reaction and was prepared by mixing equal volumes of Fe 2+ The aqueous solution and H2O2 aqueous solution were prepared, and the hydroxyl radical concentration was based on Fe 2+ The final concentration is taken as the basis), and a 2 mL standard solution is prepared; the standard solution is reacted at room temperature for 25 minutes, and then the circular dichroism spectrum of the standard solution is measured; a relationship curve of "hydroxyl radical concentration and circular dichroism signal intensity" is established, and the circular dichroism signal intensity is the absolute value of the circular dichroism signal peak at 385 nm.

[0041] Detection Example 4: Dual signal detection of hydroxyl radical aqueous solution of unknown concentration by chiral nanocomposite UCNPs@L-POM

[0042] 1 mL of 6 groups of unknown concentrations of hydroxyl radical solutions were added to 1 mL of chiral nanocomposite UCNPs@L-POM aqueous solution (5 mg / mL) to prepare 2 mL of the test solution. The obtained mixed solution was reacted at room temperature for 25 minutes, and the upconversion luminescence spectra of the 1st to 3rd groups of test solutions and the upconversion luminescence spectra and circular dichroism spectra of the 4th to 6th groups of test solutions were measured. The upconversion fluorescence intensity and circular dichroism signal intensity were respectively substituted into the relationship curve of "hydroxyl radical concentration and upconversion luminescence fluorescence intensity" and the relationship curve of "hydroxyl radical concentration and circular dichroism signal intensity", so as to calculate the concentration of hydroxyl radicals and compare it with the actual value of hydroxyl radical concentration. The relevant data and results are shown in Table 1.

[0043] Table 1: Calculation of the concentration of hydroxyl radicals in a solution of unknown concentration based on the upconversion luminescence signal intensity and the circular dichroism signal intensity

[0044]

[0045]

[0046] It should be noted that: unlike the direct detection principle of circular dichroism signals, upconversion luminescence signals are affected by the energy transfer efficiency between donors and acceptors. Therefore, compared with circular dichroism signals, the detection sensitivity of upconversion luminescence signals is lower, and the detection linear range (10-800 μM) is much larger than the linear range (1-80 μM) of circular dichroism signals. Therefore, the actual concentration of hydroxyl radicals calculated when detecting within the linear range of upconversion luminescence signals is much larger than the concentration of hydroxyl radicals calculated when detecting within the linear range of circular dichroism signals. However, since the upconversion luminescence signal of the probe mainly plays a positioning role in biological imaging, the wider detection linear range in the solution does not affect the performance of the probe in biological applications.

Claims

1. A method for preparing a chiral nanocomposite material for hydroxyl radical dual signal sensing, the steps of which are as follows: (1) Synthesis of core-shell NaErF4:0.5% Tm@NaLuF4 upconversion nanoparticles: 0.995 mmol ErCl3·6H2O, 0.005 mmol TmCl3·6H2O, 14 mL 1-Octadecene and 6 mL of oleic acid were mixed and stirred for 20 to 40 minutes, and the resulting solution was heated to 150 to 160° C. and stirred for 20 to 40 minutes until the solid in the solution was dissolved; then the temperature was naturally lowered to 45 to 55° C., 10 mL of a methanol solution containing 2.50 mmol of sodium hydroxide and 4.00 mmol of ammonium fluoride was added, and the mixture was heated to 65 to 75° C. and stirred for 20 to 40 minutes until the methanol was completely removed; the resulting mixture was heated to 300 to 320° C. and reacted for 60 to 70 minutes. After the reaction was completed, the solution was naturally cooled to 45 to 55° C., washed with acetone and ethanol, and centrifuged to obtain NaErF4: 0.5% Tm bare core upconversion nanoparticles; finally, the obtained bare core upconversion nanoparticles were dissolved in 8 mL of cyclohexane for standby use, and the concentration of the bare core upconversion nanoparticles was 125 mM; during the entire experiment, nitrogen flow was ensured to remove oxygen in the reaction system; 0.50mmol LuCl3·6H2O, 7mL 1-octadecene and 3mL oleic acid were mixed and stirred for 20-40 minutes. The resulting solution was heated to 150-160℃ and stirred for 20-40 minutes until the solid dissolved in the solution. After the temperature was naturally cooled to 45-55℃, 4mL, 125mM NaErF4: 0.5% Tm bare core upconversion nanoparticles in cyclohexane solution, and heated to 80-90°C and stirred for 20-40 minutes until the cyclohexane is completely removed; after naturally cooling to 45-55°C, 5mL of methanol solution containing 1.25mmol sodium hydroxide and 2.00mmol ammonium fluoride is added, and heated to 65-75°C and stirred for 20-40 minutes until the methanol is completely removed; then the solution is heated to 300-320°C and reacted for 60-70 minutes. After the reaction, the solution is naturally cooled to 45-55°C, washed with acetone and ethanol, and centrifuged to obtain NaErF4: 0.5% Tm@NaLuF4 core-shell structure upconversion nanoparticles; finally, the obtained core-shell structure upconversion nanoparticles are dissolved in 4mL of cyclohexane for standby use, and the concentration of the core-shell structure upconversion nanoparticles is 125mM; during the entire experiment, nitrogen gas circulation is ensured to remove oxygen in the reaction system; (2) Preparation of hydrophilic NaErF4: 0.5% Tm@NaLuF4 upconversion nanoparticles: First, add 2 mL of 125 mM NaErF4: 0.5% Tm@NaLuF4 core-shell structure upconversion nanoparticles cyclohexane solution obtained in step (1) to 2 mL of 0.1 M dilute hydrochloric acid aqueous solution, and stir for 8 to 12 hours to remove oleic acid ligands; then add acetone to precipitate ligand-free hydrophilic NaErF4: 0.5% Tm@NaLuF4 upconversion nanoparticles (UCNPs), collect by centrifugation, and disperse in 4 mL of deionized water to obtain an aqueous solution of UCNPs, wherein the concentration of the ligand-free hydrophilic NaErF4: 0.5% Tm@NaLuF4 upconversion nanoparticles is 62.5 mM; (3) Preparation of oxidized molybdenum-based polyoxometalate (Ox-POM) nanoparticles: 1 mmol (1.23586 g) of (NH4)6Mo7O 24 4H2O was dissolved in 10mL of deionized water, and 0.6mmol (0.07196g) of NaH2PO4 was dissolved in 5mL of deionized water; the two solutions were then mixed and stirred for 20-40 minutes to form Ox-POM nanoparticles; the Ox-POM nanoparticles were precipitated with 50mL of ethanol, and the Ox-POM nanoparticle precipitate was collected after centrifugation at 8000-12000rpm for 5-15min, and the obtained Ox-POM nanoparticles were then vacuum dried at 50-70°C overnight; (4) Preparation of chiral nanocomposite UCNPs@L-POM: 10 mg of dried Ox-POM nanoparticles obtained in step (3) was dissolved in 1600 μL of deionized water, 400 μL of 62.5 mM UCNPs aqueous solution obtained in step (2) was added and stirred for 3 to 10 min, then 8 mL of 31.25 mg / mL L-Cys aqueous solution was added and ultrasonication was continued for 10 to 20 minutes, the obtained UCNPs@L-POM solution was allowed to stand for 2 to 4 days, and UCNPs@L-POM powder was obtained after freeze-drying, i.e., chiral nanocomposite material for dual-signal sensing of hydroxyl radicals.

2. A chiral nanocomposite material for dual-signal sensing of hydroxyl radicals, characterized in that: The method is prepared by the method of claim 1.

3. Use of the chiral nanocomposite material for dual-signal sensing of hydroxyl radicals as claimed in claim 2 in dual-signal sensing of hydroxyl radical upconversion luminescence and circular dichroism signals.

4. The use of a chiral nanocomposite material for dual-signal sensing of hydroxyl radicals as claimed in claim 3 in dual-signal sensing of hydroxyl radical upconversion luminescence and circular dichroism signals, characterized in that: Take UCNPs@L-POM powder and add deionized water to prepare 1mL, 5mg / mL UCNPs@L-POM aqueous solution, add 1mL, 10-800μM hydroxyl radical aqueous solution to prepare 2mL standard solution; react the standard solution at room temperature for 20-30 minutes, and then measure the upconversion emission spectrum of the standard solution; establish a "relationship curve between hydroxyl radical concentration and upconversion luminescence intensity"; or take UCNPs@L-POM powder and add deionized water to prepare 1mL, 5mg / mL UCNPs@L-POM aqueous solution, add 1mL, 1-80μM hydroxyl radical aqueous solution to prepare 2mL standard solution; react the standard solution at room temperature for 20-30 minutes, and then measure the circular dichroism spectrum of the standard solution; establish a "relationship curve between hydroxyl radical concentration and circular dichroism signal intensity"; the integral wavelength range of the upconversion luminescence intensity is 600-700nm, and the circular dichroism signal intensity is the absolute value of the circular dichroism signal peak at 385nm.

5. The use of a chiral nanocomposite material for dual-signal sensing of hydroxyl radicals as claimed in claim 3 in dual-signal sensing of hydroxyl radical upconversion luminescence and circular dichroism signals, characterized in that: Take UCNPs@L-POM powder and add deionized water to prepare 1 mL, 5 mg / mL UCNPs@L-POM aqueous solution, add 1 mL of hydroxyl radical solution of unknown concentration thereto, and obtain 2 mL of the test solution; react the test solution at room temperature for 20 to 30 minutes, and then measure the upconversion emission spectrum and circular dichroism spectrum of the test solution respectively; substitute the upconversion fluorescence intensity and circular dichroism signal intensity into the relationship curve of "hydroxyl radical concentration and upconversion luminescence intensity" and "hydroxyl radical concentration and circular dichroism signal intensity" obtained in step (5), respectively, to calculate the concentration of hydroxyl radicals; the integral wavelength range of the upconversion luminescence intensity is 600 to 700 nm, and the circular dichroism signal intensity is the absolute value of the circular dichroism signal peak at 385 nm.